Efficacy and safety of negative pressure versus natural drainage after thyroid surgery: A systematic review and meta-analysis. Issue 31 (August 2018) - Li, Lei; Liu, Weizhen; Tao, Huishan; Chen, Hengyu; Li, Wenrong; Huang, Tao; Zhao, Ende
Abstract: Background: To evaluate whether negative pressure drainage has advantage over natural drainage in effectiveness and safety for patients with thyroid disease after thyroid surgery. Method: We performed intensive literature search and followed the standards described in preferred reporting items for systematic review and meta-analysis (PRISMA) statement to conduct this systematic review. Risk of bias was assessed using the Cochrane Risk of bias tool. We used Grading of Recommendations Assessment, Development and Evaluation (GRADE) system to evaluate the quality of evidence body. Results: Total 1195 participants with thyroid disease from 13 studies were included. For patients underwent thyroidectomy without neck dissection, negative pressure drainage group has a lower risk of seroma and wound infection. The duration of tube placement was shorter in negative pressure drainage group, which produced more fluid than natural drainage in the first 24-hour period. The effect of negative pressure drainage on reoperative rates, mortality, and length of hospitalization remains unclear. Conclusions: For patients underwent thyroidectomy with neck dissection, the difference between negative and natural pressure drainage groups remains uncertain due to sparse data. The quality of evidence for the above findings is low. The risk of bias for the studies is also serious. Therefore, more randomized or non-randomized controlled trials with larger sample sizes are required. Abstract : Supplemental Digital Content is available in the text